Prevalence, incidence and risk factors of subclinical mastitis in specialized dairies in Colombia - Medrano-Galarza, Catalina; Ahumada Beltrán, Diego Germán; Romero Zúñiga, Juan José; Donado Godoy, Pilar (Agronomía Mesoamericana, 2021)
Introduction. Subclinical mastitis (SCM) is one of the main diseases in cattle; studying its epidemiology is essential to implement health programs. Objective. To determine the prevalence, incidence, and factors associated with subclinical mastitis in specialized dairies in Cundinamarca, Colombia. Materials and methods. An observational-analytical, prospective-cohort study was performed. Fifteen farms were visited three times every 56 days (September-2019 to February-2020). At each visit, the California test (CMT) was performed and dirtiness of udders and hind limbs of milking cows was evaluated; likewise, milking routine was evaluated. One milk sample per farm was collected to determine somatic cell counts (SCC) and bacteria count (BC). Logistic regression mixed models were used to determine factors associated with having or acquiring SCM, and generalized linear models to determine factors associated with the probability of a greater prevalence of SCM and BC. 960 CMT were performed on 454 cows. Results. A total of 960 CMT were performed on 454 cows. The median herd-level prevalence of SCM was 50 % and it was directly associated with SCC and BC. The median cumulative herd-level incidence of developing a new and a chronic infection of SCM was 42 % and 75 %, respectively. Factors associated with having SCM were: multiparous cows (Odds Ratio, OR≥2.35), late lactation (OR=3.39), no pre-dipping (OR=1.74), and over-milking (OR=1.96). Factors that reduced the risk of acquiring SCM were: having <3 lactations (OR≤0.29), early-mid lactation (OR≤0.32), segregating cows (OR=0.37), and pre-sealing (OR=0.27). Factors associated with the probability of a greater prevalence of SCM were: not segregating (OR=2.42) and not pre-dipping (OR=2.50). Factors associated with increased BC were: dirty udders, pre-sealer action time less than 30 s, and having more than one milker. Conclusion. Multiparous cows, late lactation (>180 days in production), not segregating, not pre-sealing, and over-milking, were factors associated with acquiring and having subclinical mastitis, therefore, they are key factors to consider in prevention and control measures.